The limits of prescription: courts and social policy in India and South Africa - Friedman, Steven; Maiorano, Diego (Taylor and Francis, 2017)
This paper explores social policy-making role of supreme courts in India and South Africa. It argues that that both significantly shaped social policy. But neither imposed its will on elected government – both recognised that judicial power is limited and sought negotiation with the government and other interests to ensure compliance with rulings. Despite the difference between them, both courts promote and support collective action by the poor or their allies in civil society. The paper traces the institutional roots of the relative strength of the two courts and their relations with their governments and links their rulings to the political environment.